God and goodness : a natural theological perspective - Wynn, Mark, 1963- (Routledge studies in the philosophy of religion., 1999)
"God and Goodness takes the experience of value as a starting point for natural theology. The book proposes that the world's goodness calls for a moral response: commitment to the goodness of the world represents a natural extension of the trust to which we aspire in our dealings with human beings. Wynn draws on aesthetic experience and the anthropological literature to show us that the beauty of the world offers a glimpse into the goodness of God - not simply in relation to the world, but in itself." "This book will be invaluable for those interested in natural theology and philosophy of religion."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved